Facile fabrication of nanofibrous network reinforced hierarchical structured porous Si3N4-based ceramics based on Si-Si3N4 binary particle-stabilized foams. Issue 2 (1st February 2019) - Ren, Bo; Liu, Jingjing; Huo, Wenlong; Gan, Ke; Lu, Yuju; Chen, Yugu; Wang, Lu; Yang, Jinlong; Huang, Yong
Abstract: A facile method for preparation of SiC nanofibrous network reinforced hierarchical structured porous Si3 N4 based ceramics via annealing Si-Si3 N4 binary particle-stabilized foam in coke bed is reported in this work for the first time. The atmosphere created by coke bed enables the fabrication of Si3 N4 based porous ceramics at 1450 °C without using sintering additives. As prepared specimens possess a relative high compressive strength due to the partial oxidation of Si3 N4 particles. This novel structure with three levels of hierarchy characterized by flexible SiC nanofibrous network, cell walls and unit cells can be characterized. The vaporization of silicon powder results in formation of Si(g), SiO(g) and allows subsequent generation of SiC nanofibrous network, leading to a considerable number of micro-pores on cell walls simultaneously. As-prepared porous ceramics contained 76.7% porosity and had compressive strength of 10.81 MPa.